Values or Activity: Reality on Early Sexual Encounter among Adolescents in Zamboanga Peninsula - Mark Angelo Cristino; Jed Patrick Catalan; Josephine Duyaguit (Philippine Association of Institutions for Research, Inc., 2018)
The burgeoning teen-pregnancy annually with victims getting younger is a severely endless problem that hitherto is superficially understood in its real context. This study aimed to determine and intensely focus on the factors that influence early sexual encounters (ESE) to both adolescent boys and girls in the Zamboanga Peninsula, Philippines. To understand the underlying real phenomenological complexities, a mixed method, specifically the Sequential Explanatory was utilized. Data were first gathered and analyzed through a cross-sectional correlational survey; followed by a Focus Group Discussion represented by the teen-dads, teen-moms, parents, and teachers. Correlational analysis showed that socio-economic and sexual desire factors were significant. However, when re-explored using qualitative research, analyzed through Mayring's Qualitative Content Analysis, economic status has no direct influential pattern to early engagement in sexual activities. For them, thematically, the quality of parental role in value formation was crucial. Given this shift, a schematic diagram was developed why teenagers nowadays engage too early sexual encounters: 1) seeking the parental role, 2) blinded to values, and 3) tearful regrets. Thus, through this realization, a proposed intervention of encapsulating culture, values, and parental involvement in the teaching strategies in the sex-education curriculum is timely.